Carbon-based material derived from biomass waste for wastewater treatment - Muhammad Shamil, Soffian; Fezrul Zackry, Abdul Halim; Mohamed Afizal, Mohamed Amin; Dayang Norafizan, Awang Chee (Elsevier, 2022)
Biomass waste has known as a new precursor for the production of carbon-based materials due to its carbon richness, low cost, ease to access, ubiquitous, renewable and environmental-friendliness. In this publication, the study on the availability of biomass waste and the carbon-based materials (CBMs) for wastewater treatment application is reviewed and addressed. This paper discussed several types of CBMs such as activated carbon, graphene, carbon nanotubes, biochar, and carbon aerogel. The production of these different CBMs and their modification are given special attention. As harmful organic, dyes, and inorganic pollutants emerging from the wastewater has caused damage to the environment and water supplies, adsorption is the most widely utilised conventional technology for the removal of hazardous pollutants due to its ease of use and relatively cheap in comparison with other emerging methods. This corresponds to the CBMs which mainly works on the adsorption mechanism to perform the wastewater treatment. There are three kinds of biomass waste being explained which are sewage sludge, lignocellulosic, and cotton-based waste. This paper also extensively summarised a multitude of aspects regarding the biomass waste and the CBMs derivation from biomass waste. The challenges on the synthesis of CBMs from biomass was also included. In summary, the conclusion and future direction of the research were also discussed.